Random Allocation in Controlled Clinical Trials: A Review - Bolaji Emmanuel Egbewale (Frontiers Media S.A., 2014)
PURPOSE: An allocation strategy that allows for chance placement of participants to study groups is crucial to the experimental nature of randomised controlled trials. Following decades of the discovery of randomisation considerable erroneous opinion and misrepresentations of its concept both in principle and practice still exists. In some circles, opinions are also divided on the strength and weaknesses of each of the random allocation strategies. This review provides an update on various random allocation techniques so as to correct existing misconceptions on this all important procedure. METHODS: This is a review of literatures published in the Pubmed database on concepts of common allocation techniques used in controlled clinical trials.  RESULTS: Allocation methods that use; case record number, date of birth, date of presentation, haphazard or alternating assignment are non-random allocation techniques and should not be confused as random methods. Four main random allocation techniques were identified. Minimisation procedure though not fully a random technique, however, proffers solution to the limitations of stratification at balancing for multiple prognostic factors, as the procedure makes treatment groups similar in several important features even in small sample trials. CONCLUSIONS: Even though generation of allocation sequence by simple randomisation procedure is easily facilitated, a major drawback of the technique is that treatment groups can by chance end up being dissimilar both in size and composition of prognostic factors. More complex allocation techniques that yield more comparable treatment groups also have certain drawbacks. However, it is important that whichever allocation technique is employed, unpredictability of random assignment should not be compromised.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.